Treatment of pancreatic cancer—neoadjuvant treatment in resectable pancreatic cancer (PDAC) - Seufferlein, Thomas; Ettrich, Thomas J. (Translational Gastroenterology and Hepatology; Vol 4 (March 2019): Translational Gastroenterology and Hepatology, 2019)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers. Curative-intended resection and adjuvant chemotherapy represents the current standard of care. Despite substantial improvements in surgical treatment and intensified adjuvant treatment with more powerful regimens over the last years even clearly resectable pancreatic cancer still has an unfavorable prognosis with a high risk of relapse. Neoadjuvant or perioperative multimodal therapies have substantially improved the outcome of other resectable gastrointestinal (GI) cancers such as esophagus and gastric cancer. It is reasonable to assume that efficient chemotherapy and or radiochemotherapy may have a similar impact on the outcome of resectable PDAC. This review is focused on neoadjuvant and perioperative treatment of resectable PDAC (no borderline resectable or locally advanced PDAC), summarizes the pros and cons for neoadjuvant treatment in the context of the current literature, and also provides an overview over the landscape of ongoing clinical trials in this up-and-coming field of PDAC therapy.